Multiple sources of soluble atmospheric iron to Antarctic waters. Issue 3 (3rd March 2016) - Winton, V. H. L.; Edwards, R.; Delmonte, B.; Ellis, A.; Andersson, P. S.; Bowie, A.; Bertler, N. A. N.; Neff, P.; Tuohy, A.
Abstract: The Ross Sea, Antarctica, is a highly productive region of the Southern Ocean. Significant new sources of iron (Fe) are required to sustain phytoplankton blooms in the austral summer. Atmospheric deposition is one potential source. The fractional solubility of Fe is an important variable determining Fe availability for biological uptake. To constrain aerosol Fe inputs to the Ross Sea region, fractional solubility of Fe was analyzed in a snow pit from Roosevelt Island, eastern Ross Sea. In addition, aluminum, dust, and refractory black carbon (rBC) concentrations were analyzed, to determine the contribution of mineral dust and combustion sources to the supply of aerosol Fe. We estimate exceptionally high dissolved Fe (dFe) flux of 1.2 × 10 −6  g m −2  y −1 and total dissolvable Fe flux of 140 × 10 −6  g m −2  y −1 for 2011/2012. Deposition of dust, Fe, Al, and rBC occurs primarily during spring‐summer. The observed background fractional Fe solubility of ~0.7% is consistent with a mineral dust source. Radiogenic isotopic ratios and particle size distribution of dust indicates that the site is influenced by local and remote sources. In 2011/2012 summer, relatively high dFe concentrations paralleled both mineral dust and rBC deposition. Around half of the annual aerosol Fe deposition occurred in the austral summer phytoplankton growth season; however, the fractional Fe solubility was low. Our results suggest that the seasonality of dFe deposition can vary and should be considered on longer glacial‐interglacial timescales. Key Points: Local and remote sources contribute to Roosevelt Island dust deposition at present Dissolved Fe in Antarctic snow appears to be related to both dust and black carbon deposition Exceptionally high black carbon, dust, and dissolved Fe concentrations in 2011/2012 austral summer